Promoting Graded Exercises To Develop The Students' Writing Skill: A Classroom Action Research In Smp 1 Boyolali Students Grade Viii Semester 2 Academic Year 2010/2011 - Ngatiyem, Ngatiyem (2012)
Writing is one of the skills which must be developed in English teaching learning. In fact, the result of the students' writing is poor. It is caused by the lack of vocabulary, lack of grammar especially past tense in using verb 2 and making a coherence text. Therefore, the objective of this research is to develop the students' writing skill using graded exercises technique. The research is carried out to maximize the students' writing skill. The type of research is an action research. It consists of two cycles. There are four steps in each cycle, namely planning, acting, observing, and reflecting. The subject of the research is the 8F students of SMP Negeri 1 Boyolali. The data were collected through several techniques. Qualitative data were collected through observation in the classroom. The data were supported with informal interviews after teaching learning process. It is carried out in order to know the students' problems in writing. Quantitative data were obtained through the results of pre test and post test. The findings show that 1) graded exercises give positive effect on the improvement of the students' writing skill from cycle to cycle. Based on the score, it can be seen that the lowest score in pre test is 47, after given the treatment in two cycles; it became 68 so the improvement is 21 points. The highest score improve 10, 4 points, from 75 became 85, 4. While the average improve 18, 6 points, from 59, 5 became 78, 1. The numbers of graduation improve 70, 8%, from 20, 8% became 91, 6%. 2. Graded exercises are very effective to develop the students' writing skill. The research findings imply that graded exercises can be an alternative technique to develop the students' writing skill. Therefore, it is recommended that English teachers apply it. It is also recommended that the institution socialize it since it is useful not only for English lesson but also for other subjects. The last is for the other researcher to develop the aspects of writing skill which has not been developed in the research.